2016
DOI: 10.1002/pbc.26344
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body mass index in long-term survivors of childhood acute lymphoblastic leukemia treated without cranial radiation and with reduced glucocorticoid therapy

Abstract: Children who did not receive cranial radiation or glucocorticoids during maintenance remain at increased risk of treatment-related increases in BMI z-score, which is associated with a loss of height z-score. Interventions designed to mediate this risk should begin early, even while children are on treatment because of the association with cardiovascular risk. Monitoring of survivors of ALL should include anthropometric measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
(79 reference statements)
5
22
1
3
Order By: Relevance
“…Evaluating the Height per Age Index most of the patients had an adequate height for their age similar to the data found in another study [17]. However, studies have observed a significant reduction in the Z-scores of Height per Age Index overtime in children with ALL [6]. Our study found a statistically significant difference in relation to height for age between M1 and M3 (p=0.016); and between M2 and M3 (p=0.006), demonstrating a possible deficit in growth over treatment.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Evaluating the Height per Age Index most of the patients had an adequate height for their age similar to the data found in another study [17]. However, studies have observed a significant reduction in the Z-scores of Height per Age Index overtime in children with ALL [6]. Our study found a statistically significant difference in relation to height for age between M1 and M3 (p=0.016); and between M2 and M3 (p=0.006), demonstrating a possible deficit in growth over treatment.…”
Section: Discussionsupporting
confidence: 80%
“…A few studies concluded that male individuals have a greater propensity to gain weight compared to female individuals during the treatment, and this is in line with the differences identified among genders in the pediatric population [23]. A retrospective study that evaluated children with ALL, analyzing the Z-scores of BMI, height and weight per gender, found that male individuals had a significantly larger BMI, while females showed a greater increase in the Z-score of BMI over seven years of follow up compared to their BMI at the time of diagnosis [6]. Other studies indicate that women are at greater risk for obesity or for persisting in a nutritional state of obesity for a longer period after chemotherapy, and it is essential to prevent weight gain and complications over the long term as a result of obesity [9], similarly to what happened with the population studied, that presented a significant difference in the BMI/A index in the female gender over time.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Las causas del incremento del szIMC pueden ser multifactoriales, y existe posibilidad de que el uso de quimioterapéuticos como los esteroides generen cambios epigenéticos que predispongan a cambios permanentes de la composición corporal 4 . El seguimiento a largo plazo de este grupo de pacientes dará luz a la persistencia o no de la ganancia de peso, y de la composición corporal como una línea de investigación prioritaria 5 . En este sentido, las historias clínicas que revisamos no contaban de forma sistemática con información relacionada con el ambiente nutricional de los pacientes como la existencia de obesidad en los padres, por ejemplo, ni los hábitos de alimentación o ejercicio antes, durante o después del tratamiento.…”
Section: Discussionunclassified
“…Los supervivientes de linfoma en la edad pediátrica pueden tener mayor riesgo de morbimortalidad por causas cardiovasculares, por lo que resulta relevante estudiar los cambios en el IMC que puede presentar esta población después de haber alcanzado la remisión de la enfermedad 5 .…”
Section: Introductionunclassified